Lessons for Reformers : How to Launch, Implement, and Sustain Regulatory Reform - International Finance Corporation; Multilateral Investment Guarantee Agency; World Bank (World Bank, Washington, DC, 2017)
An Analysis of Six Case Studies in Developing and High-Income Countries